2013
DOI: 10.1017/thg.2013.19
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral Genetic Analysis of Alexithymia and the Dark Triad Traits of Personality

Abstract: The present study is the first to assess phenotypic correlations between alexithymia and the Dark Triad traits of personality in a community sample, as well as the common genetic and environmental factors underlying these correlations. Participants were 232 North American adult twin pairs who completed the Narcissistic Personality Inventory, the Self-Report Psychopathy Scale, the MACH-IV, and the Toronto Alexithymia Scale. Results revealed that alexithymia correlates significantly and positively with psychopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 59 publications
3
16
0
2
Order By: Relevance
“…A major difference between these two studies is that while our data included individuals stabilized on methadone, de Haan's sample was undergoing detoxification and the observed changes in alexithymia may reflect dynamic withdrawal symptoms. Other work has suggested that alexithymia is a stable personality trait (Tolmunen et al, 2011), and it has been shown that genetic factors may contribute to alexithymia (Cairncross et al, 2013;Ham et al, 2005). Taken together with the present work showing little change over the follow-up, it appears that alexithymia is relatively stable in this population, regardless of variation in frequency of drug use over time.…”
Section: Discussionsupporting
confidence: 75%
“…A major difference between these two studies is that while our data included individuals stabilized on methadone, de Haan's sample was undergoing detoxification and the observed changes in alexithymia may reflect dynamic withdrawal symptoms. Other work has suggested that alexithymia is a stable personality trait (Tolmunen et al, 2011), and it has been shown that genetic factors may contribute to alexithymia (Cairncross et al, 2013;Ham et al, 2005). Taken together with the present work showing little change over the follow-up, it appears that alexithymia is relatively stable in this population, regardless of variation in frequency of drug use over time.…”
Section: Discussionsupporting
confidence: 75%
“…These traits have often been associated with negative aspects of personality; for instance, psychopathy is related to higher levels of aggressiveness and impulsivity (Kennealy et al, 2010), Machiavellianism is linked to hypocrisy and manipulation (Paulhus & Williams, 2002), and narcissism is linked to dominance, superiority and egocentric attitude (Paulhus & Williams, 2002). Among these undesirable outcomes we can also find emotional deficits such as anxiety or low empathy associated with the three DT traits (Megías et al, 2018; Miller et al, 2010; Jonason & Kroll, 2015), as well as difficulty in regulating mood and alexithymia associated with psychopathy and Machiavellianism (Miao et al, 2019; Cairncross et al, 2013). The aim of the current study was to explore how the three personality traits comprising the DT could be related to depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason accounting for correlations between humor styles and alexithymia in the above study is that both correlate with empathy. Affiliative humor (i.e., positively involving others and enhancing social interaction) and self-enhancing humor (i.e., enhancing the self) show a significantly positive correlation with empathy [106] that in turn is negatively correlated with alexithymia [107]. Moreover, a negative correlation between aggressive humor and empathy has been reported [106].…”
Section: Resultsmentioning
confidence: 99%